2000
DOI: 10.1128/aem.66.8.3290-3296.2000
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bacterial Community Structure in the Colon of Pigs Fed Different Experimental Diets and after Infection with Brachyspira hyodysenteriae

Abstract: Bacterial communities in the large intestines of pigs were compared using terminal restriction fragment length polymorphism (T-RFLP) analysis targeting the 16S ribosomal DNA. The pigs were fed different experimental diets based on either modified standard feed or cooked rice supplemented with dietary fibers. After feeding of the animals with the experimental diets for 2 weeks, differences in the bacterial community structure in the spiral colon were detected in the form of different profiles of terminal restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
155
5
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(174 citation statements)
references
References 36 publications
7
155
5
1
Order By: Relevance
“…DNA was extracted from intestinal luminal contents by a bead-beating method as previously described (21). Briefly, 200 mg of intestinal content was suspended in 600 l of phosphate-buffered saline, vortexed, and centrifuged 2 min at 200 ϫ g. After transfer to a new tube, the sample was centrifuged at 12,000 ϫ g for 5 min and the pellet was resuspended in 570 l of TE (10 mM Tris-HCl-1 mM EDTA [pH 8.0]).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from intestinal luminal contents by a bead-beating method as previously described (21). Briefly, 200 mg of intestinal content was suspended in 600 l of phosphate-buffered saline, vortexed, and centrifuged 2 min at 200 ϫ g. After transfer to a new tube, the sample was centrifuged at 12,000 ϫ g for 5 min and the pellet was resuspended in 570 l of TE (10 mM Tris-HCl-1 mM EDTA [pH 8.0]).…”
Section: Methodsmentioning
confidence: 99%
“…Before DNA purification, the supernatant was treated with proteinase K (Qiagen, Hilden, Germany) at 56°C for 1 h. DNA was then purified using cetyltrimethylammonium bromide (32), and after centrifugation of the supernatant/phenol/ chloroform/isoamyolalchohol mixture, the DNA was extracted using a 6% Chelax solution (10%, Bio-Rad, Munich, Germany). The bacterial DNA was stored at Ϫ20°C until used for PCR analysis, as previously described (27), with minor modifications. Briefly, the DNA was amplified with the fluorescently labeled 5ЈFAM (carboxy-fluorescein-N-hydroxysuccinimide ester-dimethyl sulfoxide) forward primer S-D-Bact-0008-a-S-20 (5Ј-AGAGTTTGATCMTGGCTCAG-3Ј) (27), and the reverse primer S-D-Bact-0926-a-A-20 (5Ј-CCGT-CAATTCCTTTRAGTTT-3Ј) (33) for 30 cycles, digested with 20 U of restriction enzyme CfoI (Boehringer Mannheim, Mannheim, Germany) for 3 h, loaded onto a denaturing polyacrylamide gel for electrophoresis, and analyzed on an automatic sequence analyzer (ABI PRISM 373 DNA sequencer, PE Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial DNA was stored at Ϫ20°C until used for PCR analysis, as previously described (27), with minor modifications. Briefly, the DNA was amplified with the fluorescently labeled 5ЈFAM (carboxy-fluorescein-N-hydroxysuccinimide ester-dimethyl sulfoxide) forward primer S-D-Bact-0008-a-S-20 (5Ј-AGAGTTTGATCMTGGCTCAG-3Ј) (27), and the reverse primer S-D-Bact-0926-a-A-20 (5Ј-CCGT-CAATTCCTTTRAGTTT-3Ј) (33) for 30 cycles, digested with 20 U of restriction enzyme CfoI (Boehringer Mannheim, Mannheim, Germany) for 3 h, loaded onto a denaturing polyacrylamide gel for electrophoresis, and analyzed on an automatic sequence analyzer (ABI PRISM 373 DNA sequencer, PE Biosystems, Foster City, CA). The lengths of terminal-restriction fragments (T-RFs) were analyzed using the Bionumerics software package v. 4.0 (Applied Maths, Austin, TX) with special emphasis on identification of fragments differentially expressed among treatment groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many of the antibiotics that prevent subclinical infections also enhance growth rate and feed efficiency (George et al, 1982;Elsasser et al, 1997;CDUFA, 1999); however, the mode of action for growth promotion has not been fully elucidated (Walton, 1982;Leser et al, 2000). In some instances, it has been shown that AGP's inhibit the growth of pathogenic bacteria, which may cause enteritis and a reduction in feed efficiency (George et al, 1982;Hofacre et al, 1998).…”
Section: Introductionmentioning
confidence: 99%